2015
DOI: 10.1093/pasj/psv090
|View full text |Cite
|
Sign up to set email alerts
|

Detection of universality of dark matter profile from Subaru weak lensing measurements of 50 massive clusters

Abstract: We develop a novel method of measuring the lensing distortion profiles of clusters with stacking the "scaled" amplitudes of background galaxy ellipticities as a function of the "scaled" centric radius according to the Navarro-Frenk-White (NFW) prediction of each cluster, based on the assumption that the different clusters in a sample follow the universal NFW profile. First we demonstrate the feasibility of this method using both the analytical NFW model and simulated halos in a suite of high-resolution N-body … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 68 publications
2
38
0
1
Order By: Relevance
“…Interpreting the effective mass from stacked lensing requires caution when the cluster sample spans a broad range of masses and redshifts (Mandelbaum et al 2005;Niikura et al 2015). If there is a significant scatter in the luminositymass relation of halos, then the halo mass distribution of a luminosity-selected sample becomes significantly broader, with the width and asymmetry of the distribution typically increasing for higher luminosity bins.…”
Section: Interpreting the Effective Halo Massmentioning
confidence: 99%
“…Interpreting the effective mass from stacked lensing requires caution when the cluster sample spans a broad range of masses and redshifts (Mandelbaum et al 2005;Niikura et al 2015). If there is a significant scatter in the luminositymass relation of halos, then the halo mass distribution of a luminosity-selected sample becomes significantly broader, with the width and asymmetry of the distribution typically increasing for higher luminosity bins.…”
Section: Interpreting the Effective Halo Massmentioning
confidence: 99%
“…Stacking the shear signal from a sample of clusters averages over the distribution of internal structures and halo triaxiality, and thus overcomes the structural biases suffered by some individual cluster mass measurements (e.g. Mandelbaum et al 2006;Johnston et al 2007;Okabe et al 2010aOkabe et al , 2013Umetsu et al 2011Umetsu et al , 2014Umetsu et al , 2015bOguri et al 2012;Leauthaud et al 2012;Miyatake et al 2013;Niikura et al 2015). We compute the average lensing signal in physical length unit centered on the respective BCGs.…”
Section: Stacked Lensing Analysismentioning
confidence: 99%
“…We model the radial mass distribution in galaxy clusters with a Navarro−Frenk−White (NFW) density profile, motivated by cosmological N-body simulations (Navarro et al 1996(Navarro et al , 1997 as well as by direct lensing observations (e.g., Newman et al 2013;Okabe et al 2013;Umetsu et al 2014Umetsu et al , 2016Niikura et al 2015;Umetsu & Diemer 2017). The radial dependence of the spherical NFW density profile is given by (Navarro et al 1996) The surface mass density Σ(R) as a function of projected clustercentric radius R is given by projecting ρ(r) along the line of sight.…”
Section: Spherical and Elliptical Mass Modelsmentioning
confidence: 99%
“…Cluster lensing observations have established that the projected total mass distribution within individual and ensemble-averaged clusters can be well described by sharply steepening density profiles (Umetsu et al 2011a(Umetsu et al , 2014Newman et al 2013;Okabe et al 2013;, with a near-universal shape (Niikura et al 2015;Umetsu & Diemer 2017), as predicted for halos dominated by collisionless DM in quasi-gravitational equilibrium (e.g., Navarro et al 1996Navarro et al , 1997. Subsequent cluster lensing studies targeting lensing-unbiased samples (Du et al 2015;Merten et al 2015;Umetsu et al 2016;Cibirka et al 2017) have shown that the degree of halo concentration derived for these clusters agrees well with theoretical models that are calibrated for recent ΛCDM cosmologies with a relatively high normalization (Bhattacharya et al 2013;Dutton & Macciò 2014;Meneghetti et al 2014;Diemer & Kravtsov 2015).…”
Section: Introductionmentioning
confidence: 99%